Long term high temperature oxidation characteristics of La and Cu alloyed ferritic stainless steels for solid oxide fuel cell interconnects - Swaminathan, Srinivasan; Lee, Young-Su; Kim, Dong-Ik (ELSEVIER SCIENCE BV, 2016)
To ensure the best performance of solid oxide fuel cell metallic interconnects, the Fe-22 wt.% Cr ferritic stainless steels with various La contents (0.006-0.6 wt.%) and Cu addition (1.57 wt.%), are developed. Long-term isothermal oxidation behavior of these steels is investigated in air at 800 degrees C, for 2700 h. Chemistry, morphology, and microstructure of the thermally grown oxide scale are examined using XPS, SEM-EDX, and XRD techniques. Broadly, all the steels show a double layer consisting of an inner Cr2O3 and outer (Mn, Cr)(3)O-4. Distinctly, in the La-added steels, binary oxides of Cr, Mn and Ti are found at the oxide scale surface together with (Mn, Cr)(3)O-4. Furthermore, all La-varied steels possess the metallic Fe protrusions along with discontinuous (Mn, Cr)(3)O-4 spinel zones at the oxide scale/metal interface and isolated precipitates of Ti-oxides in the underlying matrix. Increase of La content to 0.6 wt.% is detrimental to the oxidation resistance. For the Cu-added steel, Cu is found to segregate strongly at the oxide scale/metal interface which inhibits the ingress of oxygen thereby suppressing the subscale formation of (Mn, Cr)(3)O-4. Thus, Cu addition to the Fe-22Cr ferritic stainless steels benefits the oxidation resistance. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: METALLIC INTERCONNECTS; CHROMIUM VAPORIZATION; ELECTRICAL-PROPERTIES; SOFC INTERCONNECT; REACTIVE ELEMENTS; STAGE OXIDATION; MODEL ALLOYS; BEHAVIOR; CR; RESISTANCE